PENGARUH PENDIDIKAN KEWIRAUSAHAAN, KREATIVITAS DAN MOTIVASI BERWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA EKONOMI UNIVERSITAS TEKNOLOGI SUMBAWA - Susi Susanti; Fendy Maradita (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the influence of entrepreneurial education, creativity, and entrepreneurial motivation on entrepreneurial intention among economics students at Universitas Teknologi Sumbawa. The rapid increase in unemployment rates, particularly among university graduates, calls for solutions such as promoting entrepreneurship as an alternative career path to address labor market imbalances. Entrepreneurship, particularly through micro, small, and medium enterprises (MSMEs), plays a vital role in regional economic growth, especially in resource-rich but underdeveloped areas like Sumbawa. This research uses a quantitative approach with a survey method, focusing on the relationship between entrepreneurial education, creativity, and motivation as independent variables, and entrepreneurial intention as the dependent variable. Data were collected from 100 respondents using a structured questionnaire, distributed through Google Forms. The findings show that entrepreneurial education, creativity, and motivation have a significant positive effect on students' entrepreneurial intentions, with motivation being the most influential factor. This research contributes to understanding how these factors can be integrated into academic curricula and policy-making to foster a more entrepreneurial mindset among students, especially in regions with abundant potential but limited infrastructure. It also highlights the importance of combining theoretical knowledge with practical business skills in higher education programs to better prepare students for entrepreneurship.